Global rate and distribution of H2 gas produced by serpentinization within oceanic lithosphere - Stacey L. Worman; Lincoln F. Pratson; Jeffrey A. Karson; Emily M. Klein (Geophysical Research Letters)
Abstract It has recently been estimated that serpentinization within continental lithosphere produces H2 at rates comparable to oceanic lithosphere (both are ~1011 mol H2/yr). Here we present a simple model that suggests that H2 production rates along the mid‐oceanic ridge alone (i.e., excluding other marine settings) may exceed continental production by an order of magnitude (~1012 mol H2/yr). In our model, H2 production rates increase with spreading rate and the net thickness of serpentinizing peridotite (S‐P) in a column of lithosphere. Lithosphere with a faster spreading rate therefore requires a relatively smaller net thickness of S‐P to produce H2 at the same rate as lithosphere with a slower rate and greater thickness of S‐P. We apply our model globally, incorporating an inverse relationship between spreading rate and net thickness of S‐P to be consistent with observations that serpentinization is more common within lithosphere spreading at slower rates.